E-Commerce untuk Strategi Peningkatan Pendapatan pada Kelompok Pengrajin Pigura â€Kliwonâ€ Kudus - Triyanto, Wiwit Agus; Zuliyati, Zuliyati (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2019)
Abstract - Data from the Department of Industry, MSMEs and Cooperatives shows that the Calligraphy Frame Craftsmen are not yet touched by their existence and are not yet recorded, where the craftsmen are one of the handicraft industries producing various kinds of frames for various calligraphy arts which are typical souvenirs for tourists. By using online-based technology through the internet, the sales transaction process can be done more easily and faster because without having to meet with buyers so that it can increase the income obtained by the group of